2017
DOI: 10.1044/2017_jslhr-l-17-0031
|View full text |Cite|
|
Sign up to set email alerts
|

Encoding Deficits Impede Word Learning and Memory in Adults With Developmental Language Disorders

Abstract: Purpose The aim of this study was to determine whether the word-learning challenges associated with developmental language disorder (DLD) result from encoding or retention deficits. Method In Study 1, 59 postsecondary students with DLD and 60 with normal development (ND) took the California Verbal Learning Test–Second Edition, Adult Version (Delis, Kramer, Kaplan, & Ober, 2000). In Study 2, 23 postsecondary students with DLD and 24 with ND attempted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 67 publications
10
45
0
Order By: Relevance
“…Groups differed on all standardized assessments, which are summarized in Table 2. All participants also participated in a study of semantic fluency and two other studies focused on vocabulary learning (Hall, McGregor, & Oleson, 2017;McGregor, Gordon, Eden, Arbisi-Kelm, & Oleson, 2017), and results supported common findings that the DLD group performs more poorly on language-learning tasks than the group with typical language. See McGregor, Gordon, et al (2017) for a more thorough discussion of participants in this study.…”
Section: Methods Participantssupporting
confidence: 72%
See 1 more Smart Citation
“…Groups differed on all standardized assessments, which are summarized in Table 2. All participants also participated in a study of semantic fluency and two other studies focused on vocabulary learning (Hall, McGregor, & Oleson, 2017;McGregor, Gordon, Eden, Arbisi-Kelm, & Oleson, 2017), and results supported common findings that the DLD group performs more poorly on language-learning tasks than the group with typical language. See McGregor, Gordon, et al (2017) for a more thorough discussion of participants in this study.…”
Section: Methods Participantssupporting
confidence: 72%
“…If we had tested a group with a wider range of abilities, we might have seen differences. However, other research groups have found differences in statistical learning and vocabulary abilities in comparisons of college students with and without DLD (Grunow et al, 2006;Plante et al, 2002;Sheng, Byrd, McGregor, Zimmerman, & Bludau, 2015), as well as in this sample (Hall, McGregor, & Oleson, 2017;McGregor, Gordon, et al, 2017). The Token Task may not have had sufficient spread to adequately show the relationship or may not have been the most sensitive test for measuring grammatical proficiency.…”
Section: Discussionmentioning
confidence: 71%
“…There have been several studies of retrieval effects on word learning in children or young adults with DLD (Chen & Liu, 2014;Haebig et al, 2019;Leonard et al, 2019;McGregor, Gordon, Eden, Arbisi-Kelm, & Oleson, 2017). Methods and retrieval schedules have differed across studies, but each investigation has reported advantages for retrieval over the comparison conditions.…”
mentioning
confidence: 99%
“…McGregor et al . (, , ) all studied young adults aged 18–25 years, and Alt and Gutmann () included those with a mean age of 19. Except for Bishop et al .…”
Section: Resultsmentioning
confidence: 99%